Efektivitas Penerapan Media Educandy Pada Siswa dalam Pembelajaran Sejarah (Penelitian Deskriptif Kualitatif di Kelas Xi SMAN 10 Bandung) - Nurjamil, Lulu (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
The purpose of this study is to find out how successful the application of educational media is to students, especially in learning history so that it becomes a medium in the form of games that educate and is conveyed in the form of historical material. The method used in this study is a qualitative descriptive method. The research results were obtained from interviews, observations, and documentation studies of the application of Educandy media during the learning process. As for the subject of this research, the students of class XI MIPA 1, XI MIPA 5, and XI MIPA 7, with each class totaling two people as representatives of the interview session, along with a history teacher with the initials LL. The results of this research include the success of the application of Educandy media, the packaging of historical materials, and the implementation of Educandy media. As for the attraction of this Educandy media, including a form of educational game-based media in history learning, the many features of the Educandy media, and of course, it has many types of word games that can be played. Then, the application of Educandy media was appointed to answer this research’s questions regarding its effectiveness.